The transition to college: lived experiences of academically talented students with autism - Austermann, Quinn; Gelbar, Nicholas W.; Reis, Sally M.; Madaus, Joseph W. (Frontiers in Psychiatry, 2023)
The experiences of autistic college students have become an increasing focus of research over the past 10 years. As a part of a larger research project, 40 successful autistic college students were interviewed about their experiences transitioning from high school to college. Participants reported being active participants in selecting colleges, but not receiving robust transition services during high school. They reported wanting additional opportunities in high school to develop executive function skills and to have more social opportunities. Further, they stressed the importance of developing greater independence while in high school.